2002
DOI: 10.1002/cne.10350
|View full text |Cite
|
Sign up to set email alerts
|

Central projections of the utricular nerve in the gerbil

Abstract: The central projections of primary afferent fibers in the utricular nerve, which convey linear head acceleration signals to neurons in the brainstem and cerebellum, are not completely defined. The purpose of this investigation was twofold: 1) to define the central projections of the gerbil utricular afferents by injecting horseradish peroxidase (HRP) and biotinylated dextran amine (BDA) into the utricular macula; and 2) to investigate the projections of individual utricular afferents by injecting HRP intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 48 publications
4
45
1
Order By: Relevance
“…It is generally agreed that, in their central representation, each endorgans has a domain of almost exclusive projection and a domain of sparse projection overlapping with other endorgans, reproducing the peripheral distribution pattern at the level of the ganglion [16,26,59,68,75]. Such a partial functional as well as anatomical overlap is best known for the frog [9,92,93].…”
Section: Establishing Central Connectionsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is generally agreed that, in their central representation, each endorgans has a domain of almost exclusive projection and a domain of sparse projection overlapping with other endorgans, reproducing the peripheral distribution pattern at the level of the ganglion [16,26,59,68,75]. Such a partial functional as well as anatomical overlap is best known for the frog [9,92,93].…”
Section: Establishing Central Connectionsmentioning
confidence: 95%
“…Clearly not enough is understood at the level of individual terminals of a given fiber to precisely predict the function of each terminal in the context of ear function as a spatial analyzer decoding threedimensional head movement to affect three-dimensional eye, neck, body movements through a three-leg reflex arc. Given that the detailed information processing from primary afferents to vestibular nuclei is only partially understood in mammals [75,98], the target for developmental processes operating in the vestibular system to form connections must be somewhat speculative. Selective ablations of function in one or more developing vestibular endorgan, while not as easy as lid suture, is now possible using specific mutations [44] and may help untangling molecular guidance and functional verification of connection formation.…”
Section: Establishing Central Connectionsmentioning
confidence: 99%
“…Fourth, CS and SS modulation in nodular Purkinje cells occurs only during roll-pitch. Modulation does not occur during yaw, even though horizontal semicircular canal primary afferents project onto granule cells in the uvula-nodulus (Kevetter and Perachio, 1986;Barmack and Shojaku, 1995;Fushiki and Barmack, 1997;Purcell and Perachio, 2001;Newlands et al, 2002;Maklad and Fritzsch, 2003). This suggests that vestibular primary afferents not only have the wrong polarity, but that their synaptic influence is too weak to account for the observed modulation of SSs.…”
Section: Antiphasic Behavior Of Css and Sssmentioning
confidence: 95%
“…They are distributed in the granule cell layer both mediolaterally and rostrocaudally over several millimeters of cerebellar cortex, in multiple folia (Kevetter and Perachio, 1986;Wu et al, 1999;Purcell and Perachio, 2001;Newlands et al, 2002;Maklad and Fritzsch, 2003). Any remaining topographic precision conveyed by mossy fiber signals to the granule cell layer is further reduced mediolaterally by the projections of parallel fibers that course through as many as 500 Purkinje cells (Brand et al, 1976;Harvey and Napper, 1991).…”
Section: Antiphasic Behavior Of Css and Sssmentioning
confidence: 99%
“…Since the CVN mediate vestibular influences on autonomic regulation, these data suggest that a large fraction of neurons in this region should receive otolith organ inputs elicited by rotations in the pitch plane. Accordingly, anatomical studies have revealed that the otolith organs provide substantial inputs to the CVN (Kevetter and Perachio 1986;Gstoettner et al 1992;Newlands et al 2002;Yingcharoen et al 2003). However, recordings in labyrinth-intact decerebrate cats indicated that the activity of virtually no CVN neurons classified as receiving otolith inputs was preferentially modulated by pitch rotations .…”
Section: Introductionmentioning
confidence: 99%